Strategi Mengoptimalisasikan Kinerja Guru Dari Aspek Disiplin Kerja, Pendidikan Dan Pelatihan, Kompetensi Dengan Motivasi Pada Sekolah Menengah Pertama Negeri 2 Musuk, Boyolali - Tri Rustami; Siti Fatonah (STIE AUB Surakarta, 2025)
The aim of this research is to analyze and provide empirical evidence of strategies for optimizing teacher performance from the aspects of work discipline, education and training, competency and motivation at State Junior High School 2 Musuk, Boyolali Regency. The population in this study were 40 teachers at State Middle School 2 Musuk, Boyolali Regency. The sampling technique used saturated sampling or census, so the number of samples in this study was 40 teachers at State Junior High School 2 Musuk, Boyolali Regency. The analysis techniques in this research are multiple linear regression path analysis, instrument tests, linearity tests and hypothesis tests which include multiple linear regression, simultaneous test (F test), partial test (t test), coefficient of determination and path analysis. The results of the t test for the first equation show that the work discipline and competency variables have a significant effect on motivation. Training education has no significant effect on motivation. The results of the t test for the second equation show that the work discipline and competency variables have a significant effect on teacher performance. Educational training and motivation have no significant effect on teacher performance. The results of the F test in the second equation show that the value of F = 33.549 is significant 0.000 <0.05, so it can be concluded that together the variables of work discipline, education, training, competence and motivation influence performance. The results of the total R2 value of 0.946 can be interpreted as variations in teacher performance at State Junior High School 2 Musuk, Boyolali Regency, explained by the variables of work discipline, education, training, competency and motivation at 94.6% and the remaining 5.4% is explained by other variables outside the research model as examples of organizational culture, organizational commitment and work environment. The results of path analysis show that the competency variable is an effective path to improving performance, the use of motivation variables as an intervening variable is not effective, but the direct influence of work discipline, education and training and competency variables is greater than the indirect influence.